2021
DOI: 10.1038/s41467-021-24337-9
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial toxin ExoU requires a host trafficking chaperone for transportation and to induce necrosis

Abstract: Pseudomonas aeruginosa can cause nosocomial infections, especially in ventilated or cystic fibrosis patients. Highly pathogenic isolates express the phospholipase ExoU, an effector of the type III secretion system that acts on plasma membrane lipids, causing membrane rupture and host cell necrosis. Here, we use a genome-wide screen to discover that ExoU requires DNAJC5, a host chaperone, for its necrotic activity. DNAJC5 is known to participate in an unconventional secretory pathway for misfolded proteins invo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…3A). Exoenzyme U (ExoU) from Pseudomonas aeruginosa T3SS has phospholipase A 2 activity that cause instant lysis of host cells ( 17 , 18 ), and substantial cell death was observed when cells were treated by PVC with ExoU in the cytotoxicity assays (Fig. 3B and fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Exoenzyme U (ExoU) from Pseudomonas aeruginosa T3SS has phospholipase A 2 activity that cause instant lysis of host cells ( 17 , 18 ), and substantial cell death was observed when cells were treated by PVC with ExoU in the cytotoxicity assays (Fig. 3B and fig.…”
Section: Resultsmentioning
confidence: 99%
“…ExoU utilizes the chaperone protein called SpcU for secretion through the T3SS [311]. ExoU also requires host DNAJC5 chaperone and ubiquitin as the cofactor for its activity within the target host cell [253][254][255][312][313][314]. The MLD (membrane localization domain) of ExoU has been mapped to residues 550-687 in its C-terminal domain [315].…”
Section: Exoumentioning
confidence: 99%
“…Quercetin is a plant-derived flavonoid that has previously been shown to inhibit DNAJC5-mediated trafficking of a bacterial toxin ( Figure 1—figure supplement 3D ; Deruelle et al, 2021 ). We found that quercetin also inhibited Nluc-α-syn secretion in a dose-dependent manner ( Figure 1—figure supplement 3E ), implying a role for endogenous DNAJC5 in α-syn secretion.…”
Section: Resultsmentioning
confidence: 99%